PENGARUH PENGGUNAAN VIDEO ANIMASI PEMBELAJARAN IPA PADA HASIL BELAJAR SISWA - Evi Mauliana,; Khairunnisa Andzani,; Rizqa Wahda Annisa,; Arita Martini, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Education is an effort to prepare the younger generation to welcome and face developments in the global era. So education must be carried out as well as possible so as to produce quality education and improve the quality of human resources. To produce quality human resources, of course, education is the main criterion. In education there is a learning process that cannot be separated from the media, methods, and learning outcomes. The media can be used by the teacher as an intermediary to convey a lesson. Learning at the elementary school level includes various subject contents combined in the form of Themes, in which there are learning material contents and one of them is Natural Sciences (IPA). In implementing it in the classroom the teacher must be able to develop students' abilities in these subjects by using and choosing the right strategies, models and media as well as creating a learning atmosphere that can increase their students' motivation to learn. There are still many students who are less motivated and do not have high curiosity in learning. The low motivation of students to learn is due to the lack of learning media that helps students in learning. To foster learning motivation and improve student learning outcomes, an innovation in learning is needed. One of the learning innovations that is appropriate and suitable for the characteristics of elementary school students for science learning is video animation. Animated videos can make it easier for students to understand learning material and can increase student interest in learning and help students understand learning material. Keywords: Education, Video Animation, Science Learning, Learning Outcomes.